The Influence of Operational Management and Marketing Strategy on the Profitability of K-24 Geliting Pharmacy in Maumere - Sukma, Firandicha Prawira; Hidayat, Dasrun; Veranita, Mira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Profitability is an important indicator of the success and sustainability of businesses in the pharmaceutical sector, including Apotek K-24 Geliting Maumere, which operates in a competitive and dynamic business environment. Efforts to increase profitability are inseparable from the role of effective operational management and targeted marketing strategies. However, the extent to which these two factors influence profitability still requires empirical evidence. Given this background, this study uses a quantitative, survey-based approach. The sampling technique used is saturated sampling, so that all 30 employees are used as research samples. Data were obtained through questionnaires and analyzed using multiple linear regression with the help of statistical software. Hypothesis testing was carried out using a t-test to see the partial effect and an F-test to see the simultaneous effect. The results of the study indicate that operational management has a significant influence on profitability, with a calculated t-value of 1.932 and a significance value of 0.004 (p < 0.05). Marketing strategy was also proven to have a significant influence on profitability, with a calculated t-value of 2.868 and a significance value of 0.008 (p < 0.05). Furthermore, the results of the F test show a calculated F value of 9.038 with a significance of 0.001, so it can be concluded that operational management and marketing strategy simultaneously have a significant effect on the profitability of Apotek K-24 Geliting Maumere.